Long-Term Impact of Bronchopulmonary Dysplasia on Pulmonary Function - Jennifer S Landry; Tiffany Chan; Larry Lands; Dick Menzies (Canadian Respiratory Journal)
BACKGROUND: Bronchopulmonary dysplasia (BPD) and the long-term respiratory consequences of prematurity are unfamiliar to adult respirologists and remain under-recognized entities to adult caregivers. In Canada, the incidence of preterm births and its main chronic respiratory complication, BPD, have increased over the past 25 years.